Which Strategies and Corresponding Competences Are Needed to Improve Supply Chain Resilience: A COVID-19 Based Review - Jethro Kiers; Jaap Seinhorst; Mirthe Zwanenburg; Klaas Stek (Logistics)
Background: During the COVID-19 pandemic, it became evident that supply chains were not as resilient as they should be. To cope with future disruptions or epidemic outbreaks, supply chain resilience should be improved based on lessons learnt from the impacts of COVID-19 to improve supply chain resilience and facilitate the corresponding competences and skills to implement strategic changes. Method: Applying the dynamic managerial capabilities theory lens, an integrative review is conducted focused on (1) the multiple impacts of COVID-19 on the supply chain resilience, (2) multiple strategies to enhance supply chain resilience, and (3) competences needed to implement the strategic changes successfully. Result: During COVID-19, supply chains could not handle supply and demand shocks, which led to a disrupted state of supply chains. To reduce the impacts of the subsequent disruptions, companies should implement specific strategic changes and increase complementary skills and competences levels. A proposed framework indicates which skills and competences need to be developed to implement a strategic change. Conclusion: Companies must shift their focus from (cost) efficiency to creating more resilient supply chains. Additionally, purchasing professionals should develop their skills and competences accordingly to cope with future disruptions.